Analysis and optimization of hot extrusion process on strenx steel 900. (2021) - Damodar Reddy, A.; Karthikeyan, P.N.; Krishnaraj, S.; Ajayan, Adarsh; Sunil Kumar Reddy, K.; Subbiah, Ram
Highlights: In present paper is focus to improve the tensile strength and hardness of the strenx steel 900 through hot extrusion process. The different input constraints are used to improve the material properties such as temperature, diameter of the orifice and extrusion force. According to their input constrains, the outcomes of tensile strength and hardness have been evaluated. The optimal constraint is found for the best performance of the process through Taguchi approach. Abstract: The substance properties are playing an essential role in materials. These properties are modified or improved through different manufacturing processes. In present paper is focus to improve the tensile strength and hardness of the strenx steel 900 through hot extrusion process. The different input constraints are used to improve the material properties such as temperature, diameter of the orifice and extrusion force. According to their input constrains, the outcomes of tensile strength and hardness have been evaluated. The optimal constraint is found for the best performance of the process through Taguchi method.